Penilaian Pendidikan Agama Kristen Berbasis Outcome-Based Education: Kerangka Konseptual dan Implikasi Pedagogis - Hutapea, Rinto Hasiholan; Panjaitan, Roimanson (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to formulate a conceptual framework for Outcome-Based Education (OBE) assessment in Christian Religious Education and to examine its pedagogical implications. Employing a qualitative approach, this conceptual study is conducted through a library research method by analyzing relevant literature on OBE, educational assessment, and Christian Religious Education. Data analysis is carried out using content analysis and conceptual synthesis. The findings indicate that OBE-based assessment in Christian Religious Education should be developed through constructive alignment among learning outcomes, performance indicators, instructional strategies, and authentic assessment covering cognitive, affective, and psychomotor domains in an integrated manner. Assessment is positioned not merely as an evaluative tool but also as a pedagogical and pastoral means that fosters faith reflection and continuous improvement. The novelty of this study lies in proposing a conceptual framework for OBE-based assessment in Christian Religious Education that integrates outcome-oriented educational principles with the transformative goals of Christian faith education.